Tingkat Depresi Lansia dengan Geriatric Depression Scale : Literature Review: Penelitian - Rizki Damayanti; Riko Sandra Putra (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Elderly individuals experiencing depression often feel isolated, lose interest in daily activities, and undergo a decline in both physical and emotional health. This study aims to determine the depression levels in the elderly using the Geriatric Depression Scale (GDS). The method employed is a literature review. The literature search strategy follows the PICOS framework, including 10 journals that were reviewed. The analysis of these ten journals revealed a variation in depression levels among the elderly. Out of a total of 586 respondents, 317 (54.1%) were categorized as normal, 175 (29.9%) experienced mild depression, 71 (12.1%) experienced moderate depression, and 23 (3.9%) experienced severe depression. The main factors influencing depression levels in the elderly include physical health decline, social isolation, and changes in social roles.